Lessons From Baltimore 1968: How History Can Heal a Harmed City - Nix, Elizabeth M. (Time Magazine, 2015)
In the 20 years that I have lived in Baltimore City, I have seen guns fired only twice; in each instance the targets were black men and the shooters were police. In one case the officer was trying to stop a group of men who had apparently stolen a car. They bailed out in front of my house, and as they were running away, the officer fired, but missed. In the second case the officer’s aim was better; an assailant held up a medical student on a bicycle, then ran through traffic right in front of our car. An off-duty cop saw the scuffle and fired. He turned out to be a 14-year-old with a BB gun. The boy lay in the street, shot in the stomach; my 12-year-old son and I waited until the police told us to move on. I called my district and set up an appointment with a detective. No one ever came to question me.
Keywords: riots of 1968; baltimore riots; history; lessons for baltimore; racial injustice